Tuning oxygen permeability in azobenzene-containing side-chain liquid crystalline polymers. Issue 7 (19th January 2016) - Hassan, Syed; Anandakathir, Robinson; Sobkowicz, Margaret J.; Budhlall, Bridgette M.
Abstract : Tuning oxygen permeability in azobenzene-containing side-chain liquid crystalline polymers was achieved by control of their mesomorphoric phases. Abstract : A series of poly[4-(4-cyanoazobenzene-4′-oxy)alkyl methacrylate]s, side-chain liquid crystalline polymers (azoLCPs) were synthesized with methylene groups as spacers varying from 5 to 12. The thermal properties and phase transition temperatures of the polymers were characterized with differential scanning calorimetry and polarized optical microscopy and a relationship between spacer lengths, glass transition ( T g ) and clearing temperatures ( T c ) of the polymers was established. The T g decreased with increasing spacer length, while the T c exibited an odd–even effect with varying spacer length. X-ray diffraction was used to determine the degree crystallinity above and below T c . The azoLCPs exhibited smectic ↔ nematic ↔ isotropic phases. Increasing crystallinity correlated linearly with decreasing gas permeability as measured using an oxygen permeation analyzer, which was used to measure the films' permeability to oxygen (O2 ) gas. Switching of the azoLCPs from a liquid crystalline to an isotropic state was accomplished by heating the films above their T c, which resulted in at least a 10-fold increase in the O2 permeability coefficient ( P O2 ). Increasing the methylene spacer length of the azoLCP had little or no effect on gas permeability however it did decrease the T c, allowing fine control of the temperature at which the switch in P O2 takes place by tuning the mesophase between nematic and isotropic states.